The social system based on tribe in Yemen and its effects on the political and cultural role of Zaidiyya - Abdülmelik El-ucri (İslami İlimler Dergisi)
This article mentions the social system based on tribe in Yemen and its effects on political and civil role of Zaydism in this region. It has been analyzed by using both classical and modern history and sociology sources in the article. Both the geographical conditions and social system based on tribe has affected the formation of Zaidiyya. By virtue of these two factors, Zaidiyya’s development and taking root in this region is analysed sociologically. Especially, al-Hâdî al-Rassî’s political experience between A.H. 284-298/897-911 in Yemen are analysed and evaluated sociologically